Noise and Critical Sound Levels During Non-Invasive Ventilation of a Preterm Infant in the Incubator - Kaiser, Elisabeth; Stutz, Regine; Goedicke-Fritz, Sybelle; Bous, Michelle; Zemlin, Michael; Adams, Christian (Klinische Pädiatrie, 2022)
Background Preterm birth and the subsequent necessary treatment in neonatal intensive care units (NICU) subjects the preterm infant to non-physiological noise exposure with potentially adverse consequences for short- and long-term development. Adjusters to improve the acoustic environment for the preterm infant need to be defined.Methods Sound pressure level measurements during routine procedures in a NICU were performed by ¼” microphones placed inside and outside the incubator. The microphones need to be suitably positioned to measure sound pressure levels that are representative for the sound field inside and outside the incubator. The sound pressure level spectra generated by respiratory support and corresponding monitor alarms were compared.Results Inside the incubator, higher sound level pressures (in dBA) were generated primarily by the use of the system components of the incubator itself than outside, whereas when the incubator was closed, it had an insulating effect on sounds generated in the NICU. Non-invasive ventilation resulted in an increase in sound pressure levels from 50 to 60 dBA in the neonate’s environment, with sound pressure levels increasing particularly in the frequency range above 1 kHz.Conclusion Preterm infants are exposed to high sound levels, especially in the non-physiological high-frequency range, particularly during non-invasive ventilation. The continuous sound exposure could be further reduced to some extent by an optimized design of the incubator.
Keywords: neonatal incubator; NICU; noise; sound pressure level spectra; respiratory support; ventilation